Danegaptide for primary percutaneous coronary intervention in acute myocardial infarction patients: a phase 2 randomised clinical trial. Issue 19 (30th March 2018) - Engstrøm, Thomas; Nepper-Christensen, Lars; Helqvist, Steffen; Kløvgaard, Lene; Holmvang, Lene; Jørgensen, Erik; Pedersen, Frants; Saunamaki, Kari; Tilsted, Hans-Henrik; Steensberg, Adam; Fabricius, Søren; Mouritzen, Ulrik; et al.
Abstract : Objectives: Reperfusion immediately after reopening of the infarct-related artery in ST-segment elevation myocardial infarction (STEMI) may cause myocardial damage in addition to the ischaemic insult (reperfusion injury). The gap junction modulating peptide danegaptide has in animal models reduced this injury. We evaluated the effect of danegaptide on myocardial salvage in patients with STEMI. Methods: In addition to primary percutaneous coronary intervention in STEMI patients with thrombolysis in myocardial infarction flow 0–1, single vessel disease and ischaemia time less than 6 hours, we tested, in a clinical proof-of-concept study, the therapeutic potential of danegaptide at two-dose levels. Primary outcome was myocardial salvage evaluated by cardiac MRI after 3 months. Results: From November 2013 to August 2015, a total of 585 patients were randomly enrolled in the trial. Imaging criteria were fulfilled for 79 (high dose), 80 (low dose) and 84 (placebo) patients eligible for the per-protocol analysis. Danegaptide did not affect the myocardial salvage index (danegaptide high (63.9±14.9), danegaptide low (65.6±15.6) and control (66.7±11.7), P=0.40), final infarct size (danegaptide high (19.6±11.4 g), danegaptide low (18.6±9.6 g) and control (21.4±15.0 g), P=0.88) or left ventricular ejection fraction (danegaptide high (53.9%±9.5%), danegaptide low (52.7%±10.3%) and control (52.1%±10.9%), P=0.64). There was no difference between groups with regard to clinical outcome. Conclusions: Administration of danegaptide to patients with STEMI did not improve myocardial salvage. Trial registration number: NCT01977755 ; Pre-results.